2016
DOI: 10.1681/asn.2015050544
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Nuclear Factor 1β–Associated Kidney Disease

Abstract: Hepatocyte nuclear factor 1b (HNF1b)-associated disease is a recently recognized clinical entity with a variable multisystem phenotype. Early reports described an association between HNF1B mutations and maturity-onset diabetes of the young. These patients often presented with renal cysts and renal function decline that preceded the diabetes, hence it was initially referred to as renal cysts and diabetes syndrome. However, it is now evident that many more symptoms occur, and diabetes and renal cysts are not alw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
129
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(139 citation statements)
references
References 52 publications
4
129
2
4
Order By: Relevance
“…In this context, renal involvement seems to be the first manifestation of MODY 5 and some of these features can be identified by antenatal ultrasound [5,6,13]. The most frequent antenatal presentation is bilateral hyperechogenic kidneys with normal or increased size [6,14].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this context, renal involvement seems to be the first manifestation of MODY 5 and some of these features can be identified by antenatal ultrasound [5,6,13]. The most frequent antenatal presentation is bilateral hyperechogenic kidneys with normal or increased size [6,14].…”
Section: Discussionmentioning
confidence: 99%
“…Decramer et al [14] screened on the diagnosis of fetal bilateral hyperechogenic kidneys and found HNF-1β mutations in 29% of the 56 newborn infants. HNF-1β appears to be a main regulator in the expression of genes of which mutations are responsible for cystic kidney diseases (Nphp1, polaris, Umod, Pkhd1, and Pkd2) [5]. The finding of polycystic kidneys is not unpredicted in patients with TCF2 mutation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations